In vivo histological evaluation of the effect of the topical application of estrogen hormone on wounds healing in ovariectomized rabbit - Bayan J Al-Kadhimy; Ban A Ghani (College of Dentistry/ University of Baghdad, 2015)
Background: Wound healing, as a normal biological process in the human body, is achieved through four precisely and highly programmed phases: hemostasis, inflammation, proliferation, and remodeling. Growth factors released in the traumatized area promote cell migration into the wound area (chemotaxis), stimulate the growth of epithelial cells and fibroblasts (mitogenesis), initiate the formulation of new blood vessels (angiogenesis), and stimulate matrix formation and remodeling of the affected region. One of factors that effects on wound healing is a sex hormones and one of these hormones is an estrogen hormone. A wide range of cutaneous cell types (eg, fibroblast, endothelial, epithelial, and inflammatory) expressed estrogen receptors, indicating potential estrogen responsiveness. Materials and methods: Thirty two female New Zealand rabbits were used in this study. All animals were ovariectomized, and incisional wounds were done on the right (experimental for estrogen hormone application) and left (control) sides of face for each animal, the control side was left to heal normally. Histological assessment regarding the count of inflammatory cells was performed for healing intervals (3, 7, 10, 14 days). Results: Topical estrogen hormone application revealed enhancement of wound healing by reducing wound size and stimulating matrix deposition in comparison to control. Conclusion: Topical estrogen cream application results in significant progress of cutaneous wound healing, leaving no scar or crust formation and can minimize the probable wound complications. Key words: Estrogen hormone, wound healing.